A case of Williams syndrome with suspected coexisting ectopic aldosterone-producing tumor in the liver. (23rd September 2020) - Baba, Shuhei; Miyoshi, Arina; Obara, Shinji; Usubuchi, Hiroaki; Terae, Satoshi; Sunahara, Masao; Oshima, Takahiro; Misawa, Kazuhito; Tsuji, Takahiro; Takahashi, Bunya; Yamazaki, Yuto; Sasano, Hironobu; et al.
Abstract : Summary: A 31-year-old man with Williams syndrome (WS) was referred to our hospital because of a 9-year history of hypertension, hypokalemia, and high plasma aldosterone concentration to renin activity ratio. A diagnosis of primary aldosteronism (PA) was clinically confirmed but an abdominal CT scan showed no abnormal findings in his adrenal glands. However, a 13-mm hypervascular tumor in the posterosuperior segment of the right hepatic lobe was detected. Adrenal venous sampling (AVS) subsequently revealed the presence of an extended tributary of the right adrenal vein to the liver surrounding the tumor. Segmental AVS further demonstrated a high plasma aldosterone concentration (PAC) in the right superior tributary vein draining the tumor. Laparoscopic partial hepatectomy was performed. The resected tumor histologically separated from the liver was composed of clear cells, immunohistochemically positive for aldesterone synthase (CYP11B2), and subsequently diagnosed as aldosterone-producing adrenal adenoma. After surgery, his blood pressure, serum potassium level, plasma renin activity and PAC were normalized. To the best of our knowledge, this is the first report of WS associated with PA. WS harbors a high prevalence of hypertension and therefore PA should be considered when managing the patients with WS and hypertension. In this case, the CT findings alone could not differentiate the adrenal rest tumor. Our case, therefore, highlights the usefulness of segmental AVS to distinguish adrenal tumors from hepatic adrenal rest tumors. Learning points: Williams syndrome (WS) is a rare genetic disorder, characterized by a constellation of medical and cognitive findings, with a hallmark feature of generalized arteriopathy presenting as stenoses of elastic arteries and hypertension. WS is a disease with a high frequency of hypertension but the renin-aldosterone system in WS cases has not been studied at all. If a patient with WS had hypertension and severe hypokalemia, low PRA and high ARR, the coexistence of primary aldosteronism (PA) should be considered. Adrenal rest tumors are thought to arise from aberrant adrenal tissues and are a rare cause of PA. Hepatic adrenal rest tumor (HART) should be considered in the differential diagnosis when detecting a mass in the right hepatic lobe. Segmental adrenal venous sampling could contribute to distinguish adrenal tumors from HART.